2007
DOI: 10.1063/1.2712957
|View full text |Cite
|
Sign up to set email alerts
|

Microwave electromagnetic and absorption properties of Nd2Fe14B∕α-Fe nanocomposites in the 0.5–18 and 26.5–40GHz ranges

Abstract: Nd 2 Fe 14 B ∕ α - Fe nanocomposites were prepared using a melt-spinning method, subsequent annealing treatment, and ball milling. The complex permittivity and permeability of the composites were measured in the 0.5–18 and 26.5–40GHz frequency ranges. The permeability spectra of the Nd2Fe14B∕α-Fe nanocomposites exhibit relaxation and resonance type characteristic in the 0.5–18 and 26.5–40GHz frequency ranges, respectively. The resonance frequency (fr) of Nd10Fe78Co5Zr1B6 nanocomposite is 30GHz due to the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…13). Experimentally, a number of studies concerning the control of the microwave properties in different types of hard/soft systems (i.e., thin films, nanocomposites and core/shell nanoparticles) can be found in the literature [45,91,123,124,129,270,271,294,[342][343][344][345][346][347][348][349][350][351][352][353][354][355]. Many studies show that µ' and µ'' depend on the ratio of hard/soft materials both for core/shell nanoparticles [129,342,345], nanocomposites [45,[347][348][349][350][351][352] and bilayers [354].…”
Section: A) B)mentioning
confidence: 99%
See 2 more Smart Citations
“…13). Experimentally, a number of studies concerning the control of the microwave properties in different types of hard/soft systems (i.e., thin films, nanocomposites and core/shell nanoparticles) can be found in the literature [45,91,123,124,129,270,271,294,[342][343][344][345][346][347][348][349][350][351][352][353][354][355]. Many studies show that µ' and µ'' depend on the ratio of hard/soft materials both for core/shell nanoparticles [129,342,345], nanocomposites [45,[347][348][349][350][351][352] and bilayers [354].…”
Section: A) B)mentioning
confidence: 99%
“…Moreover, the patents on core/shell nanoparticles and the studies on nanocomposite materials (i.e., not core/shell) have also shown that other hard materials may be potentially interesting as reflection loss materials, e.g. FeNdN [82] and FeNdB [351]. The different core/shell systems have shown advances in diverse aspects of reflection loss: increase in R L [91,124,129,270,271,294,342,[344][345][346] (see Fig.…”
Section: Microwave Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a film with perfect orientation and limited skin Crit_skin_LL31.doc p. 7 28/11/2007 effect, this quantity represents the saturation magnetization :…”
Section: A Application To Soft Thin Films With Uniform Magnetizationmentioning
confidence: 99%
“…High frequency inductors, 1 magnetic recording write heads, broadband skin antennas, 2 microwave filters, 3,4 noise suppressors 5 and Radar Absorbing materials 6,7 require high broadband permeability levels at elevated frequencies. However, it has been known since the work of Snoek 8 that there exist tradeoffs between high permeability levels and operation at elevated frequencies, i.e.…”
Section: Introductionmentioning
confidence: 99%